2014
DOI: 10.1021/jp503744x
|View full text |Cite
|
Sign up to set email alerts
|

Single-Sheeted Double Many-Body Expansion Potential Energy Surface for Ground-State ClO2

Abstract: A global single-sheeted double many-body expansion potential energy surface is reported for the ground electronic state of ClO2. The potential energy surface is obtained by fitting 3200 energy points that map all atom-diatom dissociation channels as well as all relevant stationary points, including the well-known OClO and ClOO structures. The ab initio calculations are obtained at the multireference configuration interaction level of theory, employing the cc-pVXZ (X = D, T) Dunning basis sets, and then extrapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…To account for the electronic basis-set incompleteness, we have extrapolated the energies to the complete basis set (CBS) limit using the uniform singlet- and triplet-pair extrapolation (USTE) method, which has been per se or jointly with its generalized version successfully employed in other recent studies of global PESs for a variety of molecular systems. The extrapolated correlation energy ( E ∞ cor ) is then obtained by fitting to the pair of MRCI+Q/AV T Z and MRCI+Q/AV Q Z calculations for every geometry, thence to the E 3 cor and E 4 cor energies. In the above equation, A 5 (0), c , α, and n are universal parameters, , namely, α = −0.375, A 5 (0) = 0.0037685459, c = −1.17847713, and n = 1.25 for the MRCI method.…”
Section: Computational Detailsmentioning
confidence: 99%
“…To account for the electronic basis-set incompleteness, we have extrapolated the energies to the complete basis set (CBS) limit using the uniform singlet- and triplet-pair extrapolation (USTE) method, which has been per se or jointly with its generalized version successfully employed in other recent studies of global PESs for a variety of molecular systems. The extrapolated correlation energy ( E ∞ cor ) is then obtained by fitting to the pair of MRCI+Q/AV T Z and MRCI+Q/AV Q Z calculations for every geometry, thence to the E 3 cor and E 4 cor energies. In the above equation, A 5 (0), c , α, and n are universal parameters, , namely, α = −0.375, A 5 (0) = 0.0037685459, c = −1.17847713, and n = 1.25 for the MRCI method.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In turn, the structure located at (β* = 0.0, γ* = 0.784) corresponds to the C 2 v minimum (MC 2 v ), which lies 34 kJ mol –1 above the C s geometry. In fact, the relative position of the C 2 v and C s minima has been the subject of some debate, , with the most recent predictions following the trend displayed by the current DMBE potential energy surface.…”
Section: Potential Energy Surfacementioning
confidence: 99%
“…The weak bonding and open-shell electronic structure of ClOO result in its notoriously difficult theoretical characterization. A multitude of single reference, multireference, ,,, and density functional theory , (DFT) studies have been performed on ClOO. For all of these studies, the reported geometries fail to agree with the experimental structure given by Endo and co-workers .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Varandas and co-workers computed a global ground state potential energy surface (PES) of the ClO 2 system using a double many-body expansion technique based on energies at MRCISD+Q extrapolated to the CBS limit. A detailed topological analysis of the surface was presented, including 10 stationary points, with ClOO as the global minimum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation